2017
DOI: 10.1038/s41598-017-12138-4
|View full text |Cite
|
Sign up to set email alerts
|

Restoring tides to reduce methane emissions in impounded wetlands: A new and potent Blue Carbon climate change intervention

Abstract: Coastal wetlands are sites of rapid carbon (C) sequestration and contain large soil C stocks. Thus, there is increasing interest in those ecosystems as sites for anthropogenic greenhouse gas emission offset projects (sometimes referred to as “Blue Carbon”), through preservation of existing C stocks or creation of new wetlands to increase future sequestration. Here we show that in the globally-widespread occurrence of diked, impounded, drained and tidally-restricted salt marshes, substantial methane (CH4) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 40 publications
7
141
0
Order By: Relevance
“…Although very episodic and highly variable, our study found generally higher rates of methane emissions from live vegetation than from ponds or BP. These values were nearly identical to past literature estimates of mean methane emissions by salt marshes (0.53 C/year from marsh, 0.33 C/year from BP, and 0.32 C/year from ponds vs. 0.46 g C/year from mean literature values; Kroeger et al, ). Given the high salinity, these values did not significantly alter the global warming potential of the wetlands (Poffenbarger et al, ; Kroeger et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although very episodic and highly variable, our study found generally higher rates of methane emissions from live vegetation than from ponds or BP. These values were nearly identical to past literature estimates of mean methane emissions by salt marshes (0.53 C/year from marsh, 0.33 C/year from BP, and 0.32 C/year from ponds vs. 0.46 g C/year from mean literature values; Kroeger et al, ). Given the high salinity, these values did not significantly alter the global warming potential of the wetlands (Poffenbarger et al, ; Kroeger et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…These values were nearly identical to past literature estimates of mean methane emissions by salt marshes (0.53 C/year from marsh, 0.33 C/year from BP, and 0.32 C/year from ponds vs. 0.46 g C/year from mean literature values; Kroeger et al, ). Given the high salinity, these values did not significantly alter the global warming potential of the wetlands (Poffenbarger et al, ; Kroeger et al, ). However, this significant difference suggests that transport of methane to the atmosphere is mediated by the belowground structures of marsh vegetation and that this factor outweighs the higher water table relative to the sediment surface found in ponds (Colmer, ; Van Der Nat & Middelburg, ).…”
Section: Discussionsupporting
confidence: 87%
“…In another case, intermittent water table drawdowns over the course of a year inhibited CH 4 fluxes enough to make a Delta wetland GHG neutral Mediterranean 3, 2013). Future restoration efforts in coastal and estuarine regions where alternative electron acceptors are present may provide the optimum climate benefit (Kroeger et al, 2017). Our results reveal that disturbance, even in highly managed restored wetlands, can take a significant GHG toll.…”
Section: Geophysical Research Lettersmentioning
confidence: 73%
“…Differing GHG flux responses to altered hydrology management are often dependent on elevation and rainfall, as managed sites with higher elevation and more stable patterns of precipitation have comparatively lower GHG emissions (Burden, Garbutt, Evans, Jones, & Cooper, ; Mazik et al, ; Negandhi et al, ). Although the vast majority of studies in our meta‐analysis investigating the effects of altered hydrology in BCEs were from saltmarsh sites, these processes are likely to be similar for mangroves (Kroeger et al, ). For naturally inundated seagrass habitats, increases in salinity to enhance carbon storage potential were achieved through reducing freshwater in‐flow.…”
Section: Discussionmentioning
confidence: 99%